Comportamento hidráulico do aquífero cárstico Lagoa do Jacaré e sua relação com o rio Verde Grande, em região de conflito hídrico no norte de Minas Gerais - Mateus Alfenas De Filippo (2022)
The Verde Grande watershed, like others in the Minas Gerais state northern region, goes through episodes of water scarcity. At the São João da Ponte municipality, there is an agricultural mega-enterprise, whose water supply and irrigation are carried out by the exploitation of groundwater via a set of tubular wells. The local surface water resource is restricted; thus, the tubular wells exploit the Lagoa do Jacaré Karstic Aquifer, with high water availability. In this study, a hydrogeological study was carried out in the area to assess the sustainability of this exploitation in terms of potential impacts to the Verde Grande river, the main river in the region, a focus of water conflicts. The questions raised are: what is the karst aquifer response in relation to groundwater exploitation? Is there a local hydraulic connection between the karst aquifer and the Verde Grande river? Aiming to answer these questions, series of hydrological and hydrogeological data were collected and analyzed between october/17 and june/19, including monthly data on pumping rates and water level from wells, discharges from the Verde Grande river, rainfall, and pumping tests were carried out in order to estimate the aquifer hydraulic parameters. The results indicate a resilient behavior of the karst aquifer against the groundwater exploitation by the set of wells, and the absence of direct hydraulic connection with the Verde Grande river in the area, contradicting the hypothesis of an impact on the water availability to this river due to localized overexploitation of groundwater.